KATALOG DARING DI INDONESIA: PENILAIAN BERDASARKAN KRITERIA KATALOG DARING GENERASI KETIGA - Permadi, Agus (BACA: Jurnal Dokumentasi dan Informasi, 2014)
This study aims to determine whether online public access catalogs (OPAC) developed by Indonesian vendors andprogrammers can be classified as the third generation catalog. OPACs in nine prominent higher learning institutionsand the Indonesian National Library were examined against Marshall Breeding’s ten criteria for third generationOPACs, e.g. Single point of entry to all library resources, State-of-the-art Web interface, Enriched content, Facetednavigation, Simple keyword search box, Relevancy, Did you mean ...?, Recommendations and related materials, Usercontribution—ratings, reviews, comments, and tagging, and RSS feed. Result of the examination showed that onlyone OPAC met four criteria, two OPACs met three criteria, two OPACs met two criteria, four OPACs met only onecriteria, and one OPAC did not meet any criteria. As a whole the ten OPACs met only six relatively easy criteria, e.g.Single point of entry to all library resources, State-of-the-art Web interface, Simple keyword search box, Enrichedcontent, User contribution¯ratings, reviews, comments, and RSS feed. It is concluded that the ten OPACs did nothave a sufficient number of the required features of the third generation catalog, and with only one OPAC met foureasy criteria there were still many things to accomplish to be able to reach the status of third generation catalog.